Functional fiber structure and producing method thereof

JP2025009335AActive Publication Date: 2025-01-20DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023112265
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20
Estimated Expiration
2043-07-07

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、低摩擦性及び耐摩耗性等のCPB(濃厚ポリマーブラシ)の機能が付与された機能性繊維構造物を提供することができる。また、本発明によれば、上記の機能性繊維構造物の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009335000001_ABST
    Figure 2025009335000001_ABST
Patent Text Reader

Abstract

To provide a functional fiber structure imparted with a function of CPB (concentrated polymer brush) such as low friction property and wear resistance.SOLUTION: A functional fiber structure comprises a fiber substrate composed of a number of fibers having a hydroxyl group, and a polymer layer provided on the surface of the fiber, which comprises a polymethacrylate grafted by bonding one terminal to a surface of the fiber, where the average thickness of the polymer layer is 50-2,000 nm, the ratio of the cross-sectional area of polymethacrylate to the surface area of the fiber is 10% or more, the number average molecular weight of polymethacrylate is 10,000-3,000,000, and a molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1-1.8.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a functional fiber structure and a method for producing the same. [Background technology]

[0002] As a method for modifying a substrate, a method is known in which a polymer having a group at its end that can adsorb or react with the substrate is applied to the substrate to provide a physically or chemically bonded polymer layer on the substrate surface. Also known is a method in which a polymerizable group provided on the substrate surface is used as a starting point to polymerize a monomer to provide a grafted polymer layer from the substrate surface.

[0003] In recent years, research has been conducted on so-called "concentrated polymer brushes," which are densely grafted onto a substrate using the technology of living radical polymerization developed in the 1990s. In these concentrated polymer brushes (hereafter simply referred to as "CPB"), polymer chains formed using vinyl monomers are grafted onto a substrate at a high density with intervals of 1 to 4 nm. In other words, within 1 nm of the substrate surface, 2 At least 0.1 molecular chains of polymer are bonded to each CPB. By modifying the surface of a substrate with this CPB or by swelling the CPB with a good solvent for polymers, the CPB exhibits characteristic functions such as low friction, inhibition of protein adsorption, non-blood clotting, prevention of biofouling, size exclusion, superhydrophilicity, superwater repellency, supercooling properties, and improved tactile properties, and these functions can be imparted to the substrate.

[0004] For example, it has been studied to apply CPB to the surface of substrates such as inorganic materials, plastics, and industrial products, including films (Patent Documents 1 and 2). In addition, a functional fiber fabric has been proposed, which is obtained by applying a liquid composition for polymerization containing multiple monomers to a fiber fabric and polymerizing the composition (Patent Document 3). Furthermore, a functional fabric with a gas deodorizing function has been proposed, in which a radically polymerizable monomer is grafted onto the threads that make up the fabric (Patent Document 4). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 198876 [Patent Document 2] JP 2019-65787 A [Patent Document 3] JP 2006-45686 A [Patent Document 4] JP 2013-155464 A Summary of the Invention [Problem to be solved by the invention]

[0006] Since CPB exhibits extremely low friction, it is expected to contribute to energy conservation in the field of tribology, such as reducing energy loss due to friction, and to address environmental issues such as reducing carbon dioxide emissions. In addition, since CPB exhibits characteristics such as low friction, size exclusion properties, protein adhesion prevention, non-blood coagulation prevention, superhydrophilicity, and superwater repellency, it is expected to provide high-performance medical devices and highly sensitive diagnostic drugs. However, functional fiber structures that have been endowed with effective properties such as low friction and wear resistance have not existed until now.

[0007] The present invention has been made in consideration of the problems of the conventional techniques, and an object of the present invention is to provide a functional fiber structure imparted with the functions of CPB (concentrated polymer brush), such as low friction and abrasion resistance, etc. Another object of the present invention is to provide a method for producing the functional fiber structure. [Means for solving the problem]

[0008] That is, according to the present invention, there is provided the following functional fiber structure. [1] A functional fiber structure comprising a fiber substrate composed of a large number of fibers having hydroxyl groups, and a polymer layer provided on the surface of the fibers, the polymer layer containing polymethacrylate grafted at one end thereof to the surface of the fibers, wherein the average thickness of the polymer layer is 50 to 2,000 nm, the ratio of the cross-sectional area of ​​the polymethacrylate to the surface area of ​​the fibers is 10% or more, the number average molecular weight of the polymethacrylate is 10,000 to 3,000,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 1.8. [2] The functional fiber structure according to [1], wherein the fiber is a cellulose-based fiber. [3] The functional fiber structure according to [1] or [2], wherein the polymethacrylate has a structural unit derived from at least one methacrylate monomer selected from the group consisting of alkali metal methacrylates, alkyl methacrylates, polyethylene glycol monomethyl ether methacrylates, dimethylaminoethyl methacrylates, diethylaminoethyl methacrylates, quaternary ammonium base-containing methacrylates, betaine structure-containing methacrylates, hydroxyalkyl methacrylates, polyfluoroalkyl methacrylates, and polydimethylsiloxane-containing methacrylates.

[0009] The present invention also provides a method for producing a functional fiber structure, as described below. [4] A method for producing a functional fiber structure according to any one of [1] to [3] above, comprising the steps of: reacting the fiber substrate with 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane to introduce a 2-bromoisobutyric acid ester group onto the surface of the fiber to obtain an initiator group-containing substrate; and performing surface-initiated living radical polymerization of the methacrylate monomer in the presence of the initiator group-containing substrate under a pressure condition of from normal pressure to 1,000 MPa to provide the polymer layer on the surface of the fiber, the polymer layer containing the polymethacrylate grafted at one end thereof by bonding to the surface of the fiber. Effect of the Invention

[0010] According to the present invention, it is possible to provide a functional fiber structure to which the functions of a CPB (concentrated polymer brush), such as low friction and abrasion resistance, are imparted. In addition, according to the present invention, it is possible to provide a method for producing the functional fiber structure. [Brief description of the drawings]

[0011] [Figure 1] 2 is an FE-SEM photograph of the fiber structure (fiber base material) of Comparative Example 1. [Diagram 2] 1 is an FE-SEM photograph of the fiber structure of Example 1. [Diagram 3] 1 is an FE-SEM photograph of a fiber structure (fiber base material) of Comparative Example 2. [Figure 4] 1 is an FE-SEM photograph of the fiber structure of Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. One embodiment of the functional fiber structure of the present invention is a fiber structure including a fiber base material composed of many fibers having hydroxyl groups, and a polymer layer provided on the surface of the fiber, the polymer layer containing polymethacrylate grafted by bonding one end to the surface of the fiber. The average thickness of the polymer layer is 50 to 2,000 nm, and the ratio of the cross-sectional area of ​​the polymethacrylate to the surface area of ​​the fiber (exclusive area ratio σ*) is 10% or more. The number average molecular weight of the polymethacrylate is 10,000 to 3,000,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.1 to 1.8. Hereinafter, the functional fiber structure of this embodiment will be described in detail.

[0013] (Textile base material) The fiber substrate is a fibrous substrate having a polymer layer, which is CPB, disposed on its surface, and is composed of a large number of fibers having hydroxyl groups. Examples of the fibers include organic fibers and inorganic fibers. Examples of the organic fibers include cellulose fibers, acrylic fibers, polyvinyl alcohol fibers, ethylene vinyl alcohol fibers, and polyolefin fibers. Examples of the inorganic fibers include glass fibers. These fibers and fiber substrates may be surface-treated. In addition, these fibers and fiber substrates may be plasma-treated or the like to impart hydroxyl groups to the fibers.

[0014] The fibers having hydroxyl groups constituting the fiber substrate are preferably cellulose-based fibers. That is, the fiber substrate is preferably a cellulose-based fiber structure composed of a large number of cellulose-based fibers. Since cellulose has hydroxyl groups derived from its structure, it can be used as is without treatment such as plasma treatment, which is preferable from the viewpoint of process simplification and quality uniformity. In addition, since cellulose is a natural material, it is easy to obtain and environmentally degradable, and therefore can contribute to carbon neutrality. Furthermore, since a large number of hydroxyl groups are present on the surface of cellulose, the polymer can be formed more densely.

[0015] The cellulose-based fibers are fibers composed of cellulose or cellulose derivatives, and examples thereof include vegetable fibers, regenerated fibers, and acetates. Specifically, vegetable fibers such as cotton and hemp; regenerated fibers such as rayon, cupra, and lyocell; acetates obtained by partially acetylating cellulose; and the like can be used. In addition, ultrafine fibers such as cellulose fibers, cellulose microfibers, and cellulose nanofibers obtained by defibrating cellulose can also be used.

[0016] The physical properties of the fibers, such as thickness, fineness, length, and specific gravity, are not particularly limited. The average diameter of the fibers is preferably 1 to 100 μm, and more preferably 2 to 50 μm. If the average diameter of the fibers is less than 1 μm, they may be too thin for the polymer layer to be formed, and the performance of the fiber structure may be difficult to maintain. On the other hand, if the average diameter of the fibers exceeds 100 μm, the texture of the fiber structure may be easily impaired. The cross-sectional shape of the fibers may be any of circular, irregular, and irregular shapes.

[0017] Examples of the form of the fiber substrate include woven fabrics, knitted fabrics, and nonwoven fabrics. The structure of the fiber substrate may be woven fabrics such as plain, twill, satin, and oxford, or knitted fabrics such as kanoko, interloop, half, denby, punch, jersey, milling, and smooth. Examples of the nonwoven fabric include dry nonwoven fabrics, wet nonwoven fabrics, spunbond nonwoven fabrics, meltblown nonwoven fabrics, and chemical bond nonwoven fabrics. The mesh size, surface density, and the like of the fiber substrate are not particularly limited. The surface density of the fiber substrate is, for example, 5 to 100 g / cm. 2 It's fine as long as it's to a certain extent.

[0018] (polymer layer) A polymer layer is provided on the surface of a large number of fibers constituting the fiber substrate. This polymer layer contains polymethacrylate grafted at one end thereof to the surface of the fiber. It is preferable that the polymer layer is substantially composed of only polymethacrylate grafted at one end thereof to the surface of the fiber.

[0019] Polymethacrylate is a polymer having a structural unit derived from a methacrylate monomer. The methacrylate monomer is preferably at least one selected from the group consisting of alkali metal methacrylate, alkyl methacrylate, polyethylene glycol monomethyl ether methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, quaternary ammonium base-containing methacrylate, betaine structure-containing methacrylate, hydroxyalkyl methacrylate, polyfluoroalkyl methacrylate, and polydimethylsiloxane-containing methacrylate. A polymer layer formed of a polymethacrylate having structural units derived from these methacrylate monomers can be swollen with various liquid media such as water, organic solvents, and ionic liquids. For this reason, a polymer layer formed of a polymethacrylate having structural units derived from a specific methacrylate monomer is provided on the surface of the fiber, and the polymer layer is swollen with a liquid medium as necessary, thereby making it possible to obtain a functional fiber structure having various properties including low friction and abrasion resistance to a higher degree.

[0020] Examples of alkali metals constituting the alkali metal methacrylate include lithium, sodium, and potassium. Since the alkali metal methacrylate is a monomer capable of ion dissociation, polymethacrylates having structural units derived from alkali metal methacrylate are highly hydrophilic. Therefore, the polymer layer containing polymethacrylate having structural units derived from alkali metal methacrylate can be swollen by water or an aqueous medium containing water and a water-soluble organic solvent as a good solvent, and can function as a hydrophilic film. In addition, polymethacrylate having structural units derived from alkali metal methacrylate may be formed by polymerizing methacrylic acid whose carboxyl group is protected by a protecting group and then removing the protecting group. Examples of methacrylic acid whose carboxyl group is protected by a protecting group include t-butyl methacrylate, benzyl methacrylate, trimethylsilyl methacrylate, and vinyl ether protected methacrylic acid.

[0021] The number of carbon atoms in the alkyl group constituting the alkyl methacrylate is preferably 1 to 22. Examples of the alkyl methacrylate include methyl methacrylate, ethyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, decyl methacrylate, dodecyl methacrylate, tridecyl methacrylate, hexadecyl methacrylate, and octadecyl methacrylate.

[0022] A polymer layer formed of a polymethacrylate having a structural unit derived from an alkyl methacrylate having an alkyl group having 1 to 6 carbon atoms can be swollen with a common organic solvent such as toluene, ethyl acetate, methyl methacrylate, tetrahydrofuran, and dimethylformamide; an ionic liquid such as 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide; or the like.

[0023] A polymer layer formed of polymethacrylate having a structural unit derived from an alkyl methacrylate having an alkyl group having 8 to 22 carbon atoms can be made into a low-friction polymer layer by swelling it with a hydrocarbon-based lubricant such as a long-chain hydrocarbon, a polyol ester (POE) such as trimethylolpropane trioleate or pentaerythritol tetraheptanoate, or a polyalphaolefin (PAO) which is an oligomer such as polyethylene poly-1-decene, in addition to the above-mentioned general organic solvents.

[0024] As the polyethylene glycol monomethyl ether methacrylate, monomethyl ether methacrylate having an ethylene glycol unit with a repeating unit number of 2 to 100 can be used. The polymer layer containing the polymethacrylate having a constitutional unit derived from the polyethylene glycol monomethyl ether methacrylate can be swollen in the above-mentioned aqueous medium and exhibits a function as a hydrophilic film. Furthermore, since it exhibits biocompatibility, it exhibits functions applicable to the medical field such as prevention of protein adhesion and blood coagulation.

[0025] A polymer layer containing polymethacrylate having a structural unit derived from dimethylaminoethyl methacrylate or diethylaminoethyl methacrylate can be swollen with an ionic liquid in addition to the above-mentioned general organic solvents. In addition, since it is a basic structural unit, it exhibits a function of capturing acidic substances. In addition, after polymerizing these methacrylate monomers, a halide such as benzyl chloride may be reacted to form a quaternary ammonium base. Furthermore, a betaine structure may be formed by reacting with 1,3-propane sultone or the like.

[0026] Examples of quaternary ammonium base-containing methacrylates include methacryloyloxycholine chloride, methacryloyloxycholine bis(trifluoromethanesulfonyl)imide, 2-(methacryloyloxy)-N-benzyl-N,N-dimethylammonium chloride, 2-(methacryloyloxy)-N,N,N-trimethylammonium methylsulfate, N-[2-(methacryloyloxy)ethyl]-N,N-diethylethane-1-ammonium bis(trifluoromethanesulfonyl)imide, and N-[2-(methacryloyloxy)ethyl]-N,N-dimethylbutane-1-ammonium bis(trifluoromethanesulfonyl)imide. Examples of good solvents for the polymer layer containing polymethacrylate having a structural unit derived from a quaternary ammonium base-containing methacrylate include the above-mentioned aqueous medium and ionic liquid. Furthermore, by swelling with these good solvents, a superhydrophilic film can be obtained.

[0027] Examples of the betaine structure-containing methacrylate include 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate, 4-[[2-((methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetate, and 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate. Examples of good solvents for the polymer layer containing polymethacrylate having a structural unit derived from the betaine structure-containing methacrylate include water, the above-mentioned aqueous medium, and ionic liquids. Furthermore, by swelling with these good solvents, a superhydrophilic film can be formed, and since it exhibits biocompatibility, it exhibits functions that can be applied to the medical field.

[0028] The number of carbon atoms of the hydroxyalkyl group constituting the hydroxyalkyl methacrylate is preferably 2 to 4. Examples of the hydroxyalkyl methacrylate include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and 4-hydroxybutyl methacrylate. Examples of good solvents for the polymer layer containing polymethacrylate having a structural unit derived from hydroxyalkyl methacrylate include the above-mentioned general organic solvents, aqueous media, and ionic liquids. In addition, by reacting with a compound capable of reacting with a hydroxyl group, it is possible to control the hydrophobicity / hydrophilicity or convert the characteristics.

[0029] The number of carbon atoms of the polyfluoroalkyl group constituting the polyfluoroalkyl methacrylate is preferably 1 to 10. Examples of the polyfluoroalkyl methacrylate include trifluoromethyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, and 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluoro-n-octyl methacrylate. Examples of good solvents for the polymer layer containing polymethacrylate having a structural unit derived from polyfluoroalkyl methacrylate include the above-mentioned general organic solvents, as well as fluorine-based solvents and fluorine-based lubricants. Examples of fluorine-based solvents and fluorine-based lubricants include 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 2,3,3,3-tetrafluoro-1-propene, and 1-chloro-2,3,3-trifluoro-1-propene. By swelling with these good solvents, functions such as low friction, water repellency, and oil repellency are exhibited.

[0030] Examples of the polydimethylsiloxane-containing methacrylate include 3-[methacryloyloxy]propyl polydimethylsiloxane butyl. Among them, it is preferable to use a methacrylate having a polydimethylsiloxane chain of 1 to 100 units. Examples of good solvents for the polymer layer containing polymethacrylate having a structural unit derived from polydimethylsiloxane-containing methacrylate include silicone oil and the like in addition to the above-mentioned general organic solvents. By swelling with these good solvents, the function as a water-repellent film is exhibited.

[0031] The polymethacrylate may be a homopolymer or a copolymer having a random structure or a block structure. The number average molecular weight (Mn) of the polymethacrylate is 10,000 to 3,000,000, preferably 50,000 to 3,000,000, and more preferably 100,000 to 1,000,000. If the Mn of the polymethacrylate is less than 10,000, the thickness of the polymer layer is insufficient. On the other hand, it is difficult to polymerize a polymethacrylate having an Mn of more than 3,000,000, and the polymer layer may become excessively thick. In this specification, the number average molecular weight (Mn) and weight average molecular weight (Mw) of the polymer are values ​​calculated as polymethyl methacrylate measured by gel permeation chromatography (GC).

[0032] The molecular weight distribution of the polymethacrylate (PDI=weight average molecular weight (Mw) / number average molecular weight (Mn)) is 1.1 to 1.8, and preferably 1.2 to 1.6. That is, the polymer layer is substantially formed of polymethacrylate having a relatively uniform molecular weight. If the PDI of the polymethacrylate exceeds 1.8, it will contain a large amount of polymer having a molecular weight outside the above-mentioned range, and polymer chains with too large a molecular weight will tend to come out from the surface of the polymer layer, which may prevent the desired performance from being exhibited.

[0033] The average thickness (film thickness) of the polymer layer is 50 to 2,000 nm, preferably 50 to 1,000 nm, and more preferably 100 to 800 nm. The average thickness (film thickness) of the polymer layer in this specification means the average thickness when the polymer layer is dried and not swollen with a liquid medium. The polymer layer constituting the functional fiber structure of this embodiment is increased in thickness by about 1.5 to 3 times by swelling with a good solvent for the polymethacrylate forming the polymer layer, and properties such as low friction and abrasion resistance are improved. If the average thickness of the polymer layer is less than 50 nm, the swelling amount is small even when the polymer layer is swollen with a liquid medium, and the effect of improving properties such as low friction and abrasion resistance is insufficient. On the other hand, if the average thickness of the polymer layer is more than 2,000 nm, the texture of the fiber structure is likely to change depending on the properties of the polymethacrylate, and the fiber structure may become sticky or hard.

[0034] The ratio of the cross-sectional area of ​​polymethacrylate to the surface area of ​​the numerous fibers constituting the fiber substrate (hereinafter also referred to as "exclusive area ratio σ*") is 10% or more, preferably 20% or more, and more preferably 30% or more. By forming a polymer layer by densely grafting polymethacrylate so that the exclusive area ratio σ* is 10% or more, properties such as low friction and abrasion resistance can be exhibited. The theoretical upper limit of the exclusive area ratio σ* (closest packed) is 100%. The exclusive area ratio σ* is, for example, 70% or less, preferably 60% or less.

[0035] The exclusive area ratio σ* is calculated by the following formula (1) 2 )" according to the following formula (2). σ = dLNAMn (1) σ* = σS × 100 (2) d: density of the polymer (polymethacrylate) L: thickness of the polymer layer NA: Avogadro's number Mn: Number average molecular weight of the polymer (polymethacrylate) S: Cross-sectional area of ​​the polymer (polymethacrylate)

[0036] The thickness of the polymer layer can be measured by a conventional method using, for example, an ellipsometer, an electron microscope, an atomic force microscope, etc. The density of the polymer can be measured by a value described in a conventional document or a value measured by a method described in JIS K 7112:1999, etc. The cross-sectional area of ​​the polymer can be determined from the repeating unit length in the fully stretched form of the polymer and the bulk density of the polymer.

[0037] Since the functional fiber structure of the present embodiment is provided with a polymer layer exhibiting characteristic properties, it is expected to be applied to a variety of fields, such as medical components, health care products, electronic materials, display materials, semiconductor materials, machine parts, sliding components, battery materials, and diagnostic materials.

[0038] <Method of manufacturing functional fiber structure> One embodiment of the method for producing a functional fiber structure of the present invention is the method for producing the functional fiber structure described above, and includes a step of obtaining an initiator group-containing substrate (step (1)) and a step of providing a polymer layer on the surface of a fiber (step (2)). In step (1), 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane is reacted with the fiber substrate to introduce a 2-bromoisobutyric acid ester group onto the surface of the fiber to obtain an initiator group-containing substrate. In step (2), in the presence of the obtained initiator group-containing substrate, a methacrylate monomer is subjected to surface-initiated living radical polymerization under pressure conditions of normal pressure to 1,000 MPa. As a result, a polymer layer containing polymethacrylate grafted by bonding one end to the surface of the fiber is provided on the surface of the fiber.

[0039] By reacting 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane with a fiber substrate, a 2-bromoisobutyric acid ester group, which is a polymerization initiation group, is introduced onto the surface of the fiber constituting the fiber substrate, and an initiator group-containing substrate can be obtained. In particular, when the fiber is a cellulose-based fiber, an initiator group-containing substrate having a high concentration of polymerization initiation groups introduced onto its surface can be obtained.

[0040] A method for reacting 2-bromoisobutyric acid bromide with a fiber substrate can be immersed in 2-bromoisobutyric acid bromide diluted with an organic solvent. A base such as pyridine may be present in the reaction solution. Alternatively, a base may be dissolved in the organic solvent, the fiber substrate may be immersed in the organic solvent, and 2-bromoisobutyric acid bromide may be dripped in to cause the reaction. Furthermore, the vapor of 2-bromoisobutyric acid bromide may be sprayed on the fiber substrate.

[0041] In addition, when a fiber substrate made of glass fiber or the like is used, it is preferable to react with 2-bromo-2-methylpropionyloxypropyl trialkylsilane. By reacting with 2-bromo-2-methylpropionyloxypropyl trialkylsilane, a polymerization initiator group can be introduced to the surface of the fiber by dealcoholization and dehydration. As the 2-bromo-2-methylpropionyloxypropyl trialkylsilane, 2-bromo-2-methylpropionyloxypropyl trimethoxysilane, 2-bromo-2-methylpropionyloxypropyl triethoxysilane, and 2-bromo-2-methylpropionyloxypropyl dimethoxyethoxysilane can be used.

[0042] As a method for reacting 2-bromo-2-methylpropionyloxypropyltrialkylsilane with a fiber substrate, a method of spraying 2-bromo-2-methylpropionyloxypropyltrialkylsilane onto the fiber substrate using a sprayer and then drying the same can be mentioned. Alternatively, the fiber substrate may be immersed in a reaction solution in which 2-bromo-2-methylpropionyloxypropyltrialkylsilane is dissolved in a solvent such as ethanol. This reaction solution may be made basic by adding an aqueous ammonia solution, or may be made acidic by adding acetic acid or hydrochloric acid.

[0043] In the presence of an initiator-containing substrate, a surface-initiated living radical polymerization of a methacrylate monomer is performed to provide a polymer layer containing polymethacrylate grafted at one end to the surface of the fiber on the fiber surface, thereby obtaining the desired functional fiber structure. Examples of surface-initiated living radical polymerization include atom transfer radical polymerization (ATRP method) performed by oxidation-reduction using a metal complex of copper or ruthenium as a catalyst; reversible catalyst-mediated polymerization (halogen exchange RCMP method) in which halogen exchange is performed using a quaternary ammonium iodide salt or the like, and polymerization proceeds with the quaternary ammonium salt as a catalyst; and the like. In other words, by performing living radical polymerization starting from the polymerization initiator group introduced on the surface of the fiber, a polymer layer with dense grafts of polymers can be formed on the surface of the fiber.

[0044] In the ATRP method, a monomer is polymerized using a metal complex. As the metal complex, a metal complex having an element of Groups 7 to 11 of the periodic table as a central metal is used. Specifically, a metal complex containing monovalent copper, divalent copper, divalent ruthenium, divalent iron, or divalent nickel can be mentioned. Among them, it is preferable to use a metal complex containing monovalent copper or divalent copper, which is inexpensive and easily available. More specifically, copper(I) chloride, copper(II) chloride, copper(I) bromide, copper(II) bromide, copper(I) iodide, and copper(II) iodide can be mentioned. When these copper metal complexes are used as polymerization catalysts, a polyamine that forms a complex is used as a ligand. Examples of the ligand include 2,2-bipyridine, dinonyl bipyridine, phenanthroline, tridimethylaminoethylamine, pentamethyldiethylenetriamine, tris[2-(dimethylamino)ethyl]amine, tris(2-picolyl)amine, and N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine, etc. The amount of the metal catalyst relative to 100 parts by mass of the monomer is preferably 0.001 to 0.1 parts by mass.

[0045] In order to prevent the deactivation of the catalyst during polymerization, a reducing agent may be used. Examples of the reducing agent include tin dilaurate and ascorbic acid. In addition, an azo-based polymerization initiator such as azobisisobutyronitrile may be added to promote polymerization.

[0046] The ATRP method may be bulk polymerization or solution polymerization using an organic solvent or the like. Examples of the organic solvent include hydrocarbon solvents, ester solvents, glycol solvents, ether solvents, amide solvents, alcohol solvents, sulfoxide solvents, urea solvents, and ionic liquids. Among them, it is preferable to use a solvent with high polarity such as an ionic liquid, since it can improve the polymerization rate and increase the thickness of the polymer layer. Examples of the ionic liquid include ionic liquids such as quaternary ammonium salts, imidazolium salts, pyridinium salts, quaternary phosphonium salts, and guanidinium salts.

[0047] In the halogen exchange RCMP method, salt compounds such as quaternary ammonium iodide salts, phosphonium iodide salts, and alkali metal iodide salts are used. The halogen exchange RCMP method is a method using commercially available organic materials and inexpensive inorganic salts, so it is preferable from the viewpoint of reducing costs and environmental burden, and is also preferable because it does not require metal removal and can simplify the process. In the halogen exchange RCMP method, the polymerization initiator group is halogen-exchanged with the salt compound to form a 2-iodoisobutyric acid ester group. Next, the salt compound acts as a catalyst to turn iodine into a radical and release it, and then a monomer is inserted into the carbon radical to polymerize. The released iodine immediately binds to prevent a termination reaction, and the polymerization proceeds in a living manner.

[0048] Among the salt compounds, examples of quaternary ammonium iodide salts include benzyltetrabutylammonium iodide, tetrabutylammonium iodide, tetraoctylammonium iodide, dedocyltrimethylammonium iodide, octadecyltrimethylammonium iodide, trioctadecylmethylammonium iodide, etc. From the viewpoint of increasing the activity and obtaining a thicker polymer with a high molecular weight, the amount of the salt compound relative to the polymerization initiator group is preferably at least an equimolar amount, more preferably at least 10 times the molar amount, and particularly preferably at least 100 times the molar amount.

[0049] The temperature during polymerization is preferably 60° C. or higher. The polymerization is preferably carried out in the presence of an organic solvent. The organic solvent is preferably an organic solvent that dissolves salts, and it is preferable to use an organic solvent having high polarity, such as an alcohol, glycol, amide, urea, sulfoxide, or ionic liquid.

[0050] In step (2), the methacrylate monomer is subjected to surface-initiated living radical polymerization under pressure conditions of normal pressure to 1,000 MPa, preferably 10 to 1,000 MPa. By transmitting pressure to the inside of the polymerization vessel through a liquid medium such as water, the termination reaction is suppressed, and polymethacrylate with a higher molecular weight can be formed. When the molecular weight of the polymethacrylate increases, the thickness of the polymer layer formed increases. By forming a thicker polymer layer, it is possible to impart unprecedented properties to the fiber substrate.

[0051] The polymerization may be carried out in a polymerization vessel. As the polymerization vessel, it is preferable to use a sealable vessel that can withstand high pressure. As the polymerization vessel, a polyethylene bottle, a PET bottle, a retort pouch, a blister container, or the like can be used. In addition, in consideration of polymerization under warming or heating conditions, it is preferable to use a polymerization vessel made of a material having heat resistance. Furthermore, it is preferable to use a polymerization vessel made of a material having properties such as chemical resistance and solvent resistance. Examples of such materials include polyolefin, fluororesin, polyester, polyamide, and engineering plastics.

[0052] When the polymerization solution is charged into the polymerization vessel, it is preferable to prevent a large space from being formed, that is, to prevent gas from getting into the polymerization vessel. Specifically, it is preferable to charge the polymerization solution to 90% or more of the vessel volume.

[0053] The molecular weight of the polymer (polymethacrylate) that forms the polymer layer can be measured by analyzing the polymer cut out from the functional fiber structure by a method such as hydrolysis. In addition, a surface-initiated living radical polymerization is carried out in a state where a compound (free initiator compound) such as ethyl 2-bromoisobutyrate, which has a structure similar to that of the polymerization initiator group, is added to the polymerization system, and the molecular weight of the free polymer generated by polymerization proceeding from the initiator group of the free initiator compound is measured. The molecular weight of the free polymer measured in this way can be estimated as the molecular weight of the polymer that forms the polymer layer.

[0054] The content of the free initiator compound in the polymerization system is preferably 0.01% by mass or less, more preferably 0.001% by mass or less. If the content of the free initiator compound is too high, the viscosity of the polymerization system may increase too much. This may make it difficult to remove the obtained functional fiber structure or take a long time to wash it. EXAMPLES

[0055] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0056] <Manufacturing of fiber structures> (Example 1 and Comparative Example 1) A4 size nonwoven fabric (100% cotton) was prepared as a fiber substrate, ultrasonically cleaned with methyl ethyl ketone (MEK), tetrahydrofuran (THF), and methanol, and then air-dried. The fiber substrate was immersed in a mixed solution of toluene / 2-bromoisobutyric acid bromide / pyridine (mass ratio = 85 / 10 / 5) for 1 hour to react, introducing 2-bromoisobutyric acid ester groups onto the fiber surface to obtain an initiator group-containing substrate. The obtained initiator group-containing substrate was washed with methanol and then air-dried. When infrared absorption was measured using an infrared spectrophotometer, it was found that the 1,720 cm -1 Absorption was confirmed, confirming that the polymerization initiation group, 2-bromoisobutyric acid ester group, had been introduced.

[0057] 0.08 parts of copper bromide, 0.004 parts of copper bromide, 0.5 parts of dinonyl bipyridine, 40 parts of polyethylene glycol monomethyl ether methacrylate (trade name "PME-400", NOF Corp.), 59 parts of anisole, and 1 part of anisole solution of 2-ethyl bromoisobutyrate (EBIB) (EBIB concentration: 0.0008%) were put into a glass sample bottle and homogenized to obtain a brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device (trade name "Marugoto Extract", Toyo Koatsu Co., Ltd.), and polymerization was performed for 1 hour under conditions of 60°C and 400 MPa. A viscous polymer solution was formed in the aluminum pouch. A portion of the polymer solution was sampled, and the molecular weight of the polymer formed was measured by gel permeation chromatography (GPC) using dimethylformamide (DMF) as a developing solvent. As a result, the number average molecular weight (Mn) of the polymer was 2,540,000 and the molecular weight distribution (PDI) was 1.27.

[0058] The contents of the aluminum pouch were taken out and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fiber structure was dried by blowing air to obtain a fiber structure (Example 1). The obtained fiber structure was observed with a field emission scanning electron microscope (FE-SEM), and the thickness of the formed polymer layer was measured at any three points, and the average value was taken as the "thickness of the polymer layer". As a result, the thickness of the polymer layer was 456 nm. In addition, the ratio of the cross-sectional area of ​​polymethacrylate to the surface area of ​​the fiber (exclusive area ratio σ*), calculated from the above-mentioned formulas (1) and (2), was 35%. An untreated nonwoven fabric (fiber substrate) was used as Comparative Example 1. An FE-SEM photograph of the fiber structure (fiber substrate) of Comparative Example 1 is shown in FIG. 1. In addition, an FE-SEM photograph of the fiber structure of Example 1 is shown in FIG. 2.

[0059] Example 2 A4-sized nonwoven fabric (100% cotton) was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.08 parts of copper bromide, 0.004 parts of copper bromide, 0.5 parts of dinonyl bipyridine, 40 parts of PME-400, 59 parts of anisole, and 1 part of anisole solution of EBIB (EBIB concentration: 0.0008%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a water bath and polymerized for 4 hours under conditions of 60°C and normal pressure (0.1 MPa). A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 600,000 and the PDI was 1.38. The contents of the aluminum pouch were removed and immersed in methanol (MeOH) for 12 hours. After ultrasonic cleaning with MeOH, the fiber structure was dried by blowing air to obtain a fiber structure (Example 2). The polymer layer of the obtained fiber structure had a film thickness of 97 nm and an occupied area ratio σ* of 33%.

[0060] Example 3 A4 size nonwoven fabric (composite fiber of 80% rayon and 20% polypropylene (PP)) was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator group-containing substrate. 0.08 parts of copper bromide, 0.004 parts of copper bromide, 0.5 parts of 2,2'-bipyridine, 40 parts of 2-hydroxyethyl methacrylate (HEMA), 59 parts of ethanol, and 1 part of an ethanol solution of EBIB (EBIB concentration: 0.0008%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator group-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device and polymerized for 6 hours under conditions of 60°C and 100 MPa. A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 230,000, and the PDI was 1.32. The contents of the aluminum pouch were removed and immersed in MeOH for 12 hours. After ultrasonic cleaning with MeOH, the fiber structure was dried by blowing air to obtain a fiber structure (Example 3). The thickness of the polymer layer of the obtained fiber structure was 210 nm, and the occupied area ratio σ* was 47%.

[0061] Example 4 A4-sized nonwoven fabric (composite fiber of 70% cotton and 30% polyester (PE)) was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.07 parts of copper bromide, 0.006 parts of copper bromide, 0.2 parts of 2,2'-bipyridine, 47 parts of dimethylaminoethyl methacrylate (DMAEMA), 47 parts of ethanol, and 0.2 parts of an ethanol solution of EBIB (EBIB concentration: 0.1%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device and polymerized for 4 hours under conditions of 40°C and 300 MPa. A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 1,250,000, and the PDI was 1.33. The contents of the aluminum pouch were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fibers were dried by blowing air to obtain a fiber structure (Example 4). The polymer layer of the obtained fiber structure had a thickness of 580 nm and an area coverage ratio σ* of 24%.

[0062] Example 5 12.2 parts of 1,3-propane sultone was placed in a glass sample tube, and 20 parts of acetonitrile and 80 parts of water were added to homogenize the mixture. The fiber structure obtained in Example 4 was immersed in the mixture, and reacted at 60°C for 12 hours using a water bath. After cooling, the contents were removed and thoroughly washed with MeOH and pure water. The mixture was dried in a blower dryer at 80°C to obtain a fiber structure (Example 5). When the infrared absorption of the obtained fiber structure was measured, a 1,030 cm peak attributable to the sulfonyl group was observed. -1 Absorption was confirmed around the wavelength of 100 nm. The thickness of the polymer layer formed was 920 nm. It is believed that the polymethacrylate was zwitterionized, increasing its molecular weight, and the cross-sectional area of ​​the polymethacrylate (polymer chain) expanded, resulting in an increase in the film thickness. The contact angle with water measured by dropping water onto the polymer layer was 8°, confirming that the polymer layer has sufficient hydrophilicity.

[0063] Example 6 A4-sized nonwoven fabric (cotton / PET / nylon composite fiber) was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.08 parts of copper bromide, 0.004 parts of copper bromide, 0.5 parts of 2,2'-bipyridine, 40 parts of tert-butyl methacrylate (t-BuMA), 59 parts of anisole, and 1 part of anisole solution of EBIB (EBIB concentration: 0.0008%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device and polymerized for 4 hours under conditions of 60°C and 100 MPa. A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 210,000, and the PDI was 1.19. The contents of the aluminum pouch were removed and immersed in THF for 12 hours. After ultrasonic cleaning with MeOH, the fibers were dried by blowing air to obtain a fiber structure (Example 6). The polymer layer of the obtained fiber structure had a thickness of 182 nm and an area ratio σ* of 42%.

[0064] Example 7 Five parts of p-toluenesulfonic acid were placed in a separable glass flask, and 95 parts of DMF were added to homogenize the mixture. The fiber structure obtained in Example 6 was immersed in the mixture, and the mixture was reacted at 80°C for 10 hours using an oil bath. After cooling, the contents were removed and thoroughly washed with MeOH and pure water. The mixture was dried in a blower dryer at 80°C to obtain a fiber structure (Example 7). When the infrared absorption of the obtained fiber structure was measured, a 1,700 cm peak attributable to the carboxyl group was observed. -1 Absorption was observed nearby.

[0065] Example 8 A glass beaker was filled with a 5% aqueous solution of sodium hydroxide. The fiber structure obtained in Example 6 was immersed in the solution to neutralize the carboxyl groups and convert them into sodium salts. The contents were removed and thoroughly washed with pure water. The fiber structure was dried in a blower dryer at 80°C to obtain a fiber structure (Example 8).

[0066] (Example 9 and Comparative Example 2) A plain weave fabric (100% cotton) of A4 size was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.02 parts of copper bromide, 0.001 parts of copper bromide, 0.1 parts of dinonyl bipyridine, 99 parts of lauryl methacrylate (LMA), and 1 part of a lauryl methacrylate solution of EBIB (EBIB concentration: 0.08%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device and polymerized for 6 hours under conditions of 60°C and 100 MPa. A viscous polymer solution was formed in the aluminum pouch. The Mn of the polymer produced was 1,630,000, and the PDI was 1.16. The contents of the aluminum pouch were taken out and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fabric was dried by blowing air to obtain a fiber structure (Example 9). The polymer layer of the obtained fiber structure had a thickness of 472 nm and an area ratio σ* of 47%. An untreated fabric (fiber substrate) was used as Comparative Example 2.

[0067] To compare water absorption, a drop of water was dropped onto the surface of each of the fiber substrate of Comparative Example 2 and the fiber structure of Example 9, and the degree of water repellency was observed. An FE-SEM photograph of the fiber structure (fiber substrate) of Comparative Example 2 is shown in FIG. 3. An FE-SEM photograph of the fiber structure of Example 9 is shown in FIG. 4. As shown in FIGS. 3 and 4, water was absorbed and penetrated into the fiber substrate of Comparative Example 2 (untreated fabric), whereas water was repelled by the fiber structure of Example 9. This indicates that the surface of the fiber substrate was hydrophobized.

[0068] Example 10 A filter (100% rayon, filtration accuracy 20-30 μm) of about 10 cm×10 cm size was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.1 parts of copper bromide, 0.004 parts of copper bromide, 0.7 parts of dinonyl bipyridine, 50 parts of polyethylene glycol monomethyl ether methacrylate (PME-400), 49 parts of anisole, and 1 part of an anisole solution of EBIB (EBIB concentration: 0.001%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device and polymerized for 4 hours under conditions of 60° C. and 100 MPa. A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 1,090,000, and the PDI was 1.65. The contents of the aluminum pouch were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fibers were dried by blowing air to obtain a fiber structure (Example 10). The polymer layer of the obtained fiber structure had a thickness of 281 nm and an area coverage ratio σ* of 52%.

[0069] Example 11 A nonwoven fabric (100% cupra) of about 10 cm x 10 cm size was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.3 parts of copper bromide, 0.02 parts of copper bromide, 2 parts of dinonyl bipyridine, 48 parts of polydimethylsiloxane-containing methacrylate (trade name "X-22-174ASX", manufactured by Shin-Etsu Chemical Co., Ltd., functional group equivalent: about 900 g / mol), 49 parts of anisole, and 1 part of an anisole solution of EBIB (EBIB concentration: 0.04%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device (trade name "PV-400", manufactured by Shin Corporation), and polymerization was carried out for 6 hours under conditions of 60°C and 300 MPa. A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 2,300,000 and the PDI was 1.27. The contents of the aluminum pouch were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the polymer was dried by blowing air to obtain a fiber structure (Example 11). The film thickness of the polymer layer of the obtained fiber structure was 553 nm, and the occupied area ratio σ* was 38%.

[0070] Example 12 A nonwoven fabric (100% cupra) of about 10 cm x 10 cm size was prepared as a fiber substrate, and 2-bromoisobutyric acid ester groups were introduced onto the fiber surface in the same manner as in Example 1 described above to obtain an initiator-containing substrate. 0.1 parts of copper bromide, 0.03 parts of copper bromide, 0.9 parts of dinonyl bipyridine, 49 parts of trifluoroethyl methacrylate (3FEMA), 49 parts of anisole, and 1 part of an anisole solution of EBIB (EBIB concentration: 0.03%) were put into a glass sample bottle and homogenized to obtain a brownish-brown polymerization solution. The initiator-containing substrate was placed in an aluminum pouch, filled with the polymerization solution, and sealed. The aluminum pouch was placed in a high-pressure device (PV-400) and polymerized for 4 hours under conditions of 60°C and 400 MPa. A viscous polymer solution was produced in the aluminum pouch. The Mn of the produced polymer was 3,490,000, and the PDI was 1.23. The contents of the aluminum pouch were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fibers were dried by blowing air to obtain a fiber structure (Example 12). The polymer layer of the obtained fiber structure had a thickness of 1,500 nm and an area ratio σ* of 20%.

[0071] The results of Examples 1 to 4, 6, and 9 to 12 are shown in Table 1.

[0072] TIFF2025009335000002.tif89170

[0073] Comparative Example 3 A4 size nonwoven fabric (100% cotton) was prepared as a fiber substrate, ultrasonically cleaned with MEK, THF, and MeOH, and then air-dried. The prepared fiber substrate was immersed in a mixed solution containing 85 parts of toluene, 10 parts of methacrylic acid bromide, and 5 parts of pyridine for 1 hour to react, and a methacrylic group, which is a polymerization reactive group, was introduced to the fiber surface via an ester bond to obtain an initiator group-imparted substrate. The obtained initiator group-containing substrate was washed with methanol and then air-dried. When infrared absorption was measured using an infrared spectrophotometer, it was found that the 1,720 cm -1 Absorption of the compound was confirmed, confirming that a methacryl group, which is a polymerization initiating group, had been introduced.

[0074] The initiator group-imparting base material and 100 parts of PME-400 were placed in a flask, and after bubbling nitrogen at 65°C for 1 hour, 0.1 parts of 2,2-azobis(2-methylpropionitrile) (AIBN) were added and reacted for 24 hours. A viscous polymer solution was produced in the flask. The Mn of the produced polymer was 450,000 and the PDI was 2.50. The contents of the flask were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the mixture was dried by blowing air to obtain a fiber structure (Comparative Example 3). The film thickness of the polymer layer of the obtained fiber structure was 13 nm, and the occupied area ratio σ* was 6%.

[0075] Comparative Example 4 A4 size nonwoven fabric (100% cotton) was prepared as a fiber substrate, ultrasonically cleaned with MEK, THF, and MeOH, and then air-dried. 90 parts of PME-400 and 10 parts of 2-isocyanatoethyl methacrylate (MOI) were placed in a flask, and nitrogen was bubbled at 65°C for 1 hour, after which 0.1 parts of AIBN was added and reacted for 24 hours. A viscous polymer solution was produced in the flask. The Mn of the produced polymer was 350,000 and the PDI was 2.34. The fiber substrate was immersed in the polymer solution and reacted at 80°C for 1 hour. The contents of the flask were removed and immersed in THF for 12 hours. After ultrasonic cleaning with THF, the fiber substrate was air-dried to obtain a fiber structure (Comparative Example 4). The film thickness of the polymer layer of the obtained fiber structure was 11 nm, and the occupied area ratio σ* was 6%.

[0076] <Evaluation> (Low friction) The manufactured fiber structure was swollen with the lubricating liquid medium shown in Table 2 and attached to a pin with a diameter of 10 mm. 3 A sliding test (reciprocating sliding, sliding width: 4 cm, load: 1 N, sliding speed: 1 cm / sec, 100 reciprocating motions) was conducted using a silicone rubber sheet (manufactured by Anton Paar Japan) with a thickness of 1 mm, and low friction was evaluated according to the following evaluation criteria. The results are shown in Table 2. A: The friction coefficient was less than 0.5. △: The friction coefficient was 0.5 or more and less than 0.8. ×: The friction coefficient was 0.8 or more.

[0077] (Wear resistance) After the above sliding test, the state of adhesion of the fibers to the silicone rubber sheet (state of remaining fibers) was visually observed, and the friction characteristics were evaluated according to the following evaluation criteria. The results are shown in Table 2. ○: No residual fibers were observed. ×: Fiber residue was observed.

[0078] TIFF2025009335000003.tif50170 [Industrial Applicability]

[0079] The functional fiber structure of the present invention is expected to be used in applications that utilize the low friction inherent to the CPB material, as well as protein adsorption inhibition, non-blood coagulation, biofouling prevention, size exclusion properties, superhydrophilicity, superwater repellency, supercooling properties, and texture improvement properties, etc. In particular, it is useful as a material for medical devices, diagnostic drugs, sanitary products, daily materials, clothing, agricultural materials, and filtration and adsorption applications.

Claims

1. A fiber base material composed of a large number of fibers having hydroxyl groups; a polymer layer disposed on the surface of the fiber, the polymer layer comprising polymethacrylate grafted at one end thereof to be bonded to the surface of the fiber; The average thickness of the polymer layer is 50 to 2,000 nm; The ratio of the cross-sectional area of ​​the polymethacrylate to the surface area of ​​the fiber is 10% or more; The polymethacrylate has a number average molecular weight of 10,000 to 3,000,000 and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.1 to 1.

8.

2. The functional fiber structure according to claim 1 , wherein the fiber is a cellulosic fiber.

3. The functional fiber structure according to claim 1, wherein the polymethacrylate has a structural unit derived from at least one methacrylate monomer selected from the group consisting of alkali metal methacrylates, alkyl methacrylates, polyethylene glycol monomethyl ether methacrylates, dimethylaminoethyl methacrylates, diethylaminoethyl methacrylates, quaternary ammonium base-containing methacrylates, betaine structure-containing methacrylates, hydroxyalkyl methacrylates, polyfluoroalkyl methacrylates, and polydimethylsiloxane-containing methacrylates.

4. A method for producing a functional fiber structure according to any one of claims 1 to 3, comprising the steps of: a step of reacting the fiber substrate with 2-bromoisobutyric acid bromide or 2-bromo-2-methylpropionyloxypropyltrialkylsilane to introduce 2-bromoisobutyric acid ester groups onto the surface of the fiber to obtain an initiator group-containing substrate; a step of subjecting the methacrylate monomer to surface-initiated living radical polymerization under a pressure condition of normal pressure to 1,000 MPa in the presence of the initiator group-containing substrate to provide the polymer layer on the surface of the fiber, the polymer layer including the polymethacrylate grafted at one end thereof by being bound to the surface of the fiber; A method for producing a functional fiber structure having the above structure.

Citation Information

Patent Citations

  • Adsorbent with enhanced ratio of polymer brush and method for removing useful or harmful material using the adsorbent

    JP2017164698A

  • Antifouling fabric and method for manufacturing the same

    JP2020133018A

  • Composition, cured film, laminate, vessel, underwater structure, medical device, and microchannel chip

    JP2021123712A

  • Virus inactivation structure

    JP2022157406A

  • Surface modified film, method for producing surface modified film, and surface modified substrate

    JP2023012123A